Can We Discern the Effect of Globalization on Income Distribution? Evidence from Household Surveys - Milanovic, Branko (Published by Oxford University Press on behalf of the World Bank, 2014)
New data derived directly from household surveys are used to examine the effects of globalization on income distribution in poor and rich countries. The article looks at the impact of openness and of direct foreign investment on relative income shares across the entire income distribution. It finds strong evidence that at low average income levels, the income share of the poor is smaller in countries that are more open to trade. As national income levels rise, the incomes of the poor and the middle class rise relative to the income of the rich. The article explains why using the trade to gross domestic product (GDP) ratio in purchasing power parity terms, as favored by some analysts, is inappropriate in studies of the effect of trade on income distribution.